Biology of Francisella tularensis subspecies holarctica live vaccine strain in the tick vector Dermacentor variabilis. - Rinosh J Mani (Public Library of Science (PLoS), 2012)
Background The γ-proteobacterium Francisella tularensis is the etiologic agent of seasonal tick-transmitted tularemia epizootics in rodents and rabbits and of incidental infections in humans. The biology of F. tularensis in its tick vectors has not been fully described, particularly with respect to its quanta and duration of colonization, tissue dissemination, and transovarial transmission. A systematic study of the colonization of Dermacentor variabilis by the F. tularensis subsp. holarctica live vaccine strain (LVS) was undertaken to better understand whether D. variabilis may serve as an inter-epizootic reservoir for F. tularensis. Methodology/principal findings Colony-reared larva, nymph, and adult D. variabilis were artificially fed LVS via glass capillary tubes fitted over the tick mouthparts, and the level of colonization determined by microbial culture. Larvae and nymphs were initially colonized with 8.8 ± 0.8 × 10(1) and 1.1 ± 0.03 × 10(3) CFU/tick, respectively. Post-molting, a significant increase in colonization of both molted nymphs and adults occurred, and LVS persisted in 42% of molted adult ticks at 126 days post-capillary tube feeding. In adult ticks, LVS initially colonized the gut, disseminated to hemolymph and salivary glands by 21 days, and persisted up to 165 days. LVS was detected in the salivary secretions of adult ticks after four days post intra-hemocoelic inoculation, and LVS recovered from salivary gland was infectious to mice with an infectious dose 50% of 3 CFU. LVS in gravid female ticks colonized via the intra-hemocoelic route disseminated to the ovaries and then to the oocytes, but the pathogen was not recovered from the subsequently-hatched larvae. Conclusions/significance This study demonstrates that D. variabilis can be efficiently colonized with F. tularensis using artificial methods. The persistence of F. tularensis in D. variabilis suggests that this tick species may be involved in the maintenance of enzootic foci of tularemia in the central United States.